Myelin-oligodendrocyte-glycoprotein (MOG) autoantibodies as potential markers of severe optic neuritis and subclinical retinal axonal degeneration - Havla, Joachim; Kümpfel, T.; Schinner, R.; Spadaro, M.; Schuh, E.; Meinl, E.; Hohlfeld, R.; Outteryck, O. (Journal of neurology, 2017)
Antibodies against conformation-dependent epitopes of myelin-oligodendrocyte-glycoprotein (MOG-abs) are present in subgroups of neuromyelitis optica spectrum disorder (NMOSD), recurrent optic neuritis (rON), multiple sclerosis (MS), and anti-NMDAR encephalitis. Using optical coherence tomography (OCT) we assessed whether MOG-abs might serve as potential marker of retinal axonal degeneration. We investigated a clinically heterogeneous cohort of 13 MOG-abs-positive patients (4 MOG-abs-positive rON, 4 MOG-abs-positive adult MS, 3 MOG-abs-positive relapsing encephalomyelitis, 2 MOG-abs-positive aquaporin-4-abs-negative NMOSD). As controls, we studied 13 age, sex and ON episode(s)-matched MOG-abs and aquaporin-4-abs-negative (AQP4-abs-negative) MS patients and 13 healthy controls (HC). In addition, we investigated 19 unmatched AQP4-abs-positive MOG-abs-negative NMOSD subjects. Considering all eyes, global pRNFL [in µm, mean (SD)] was significantly reduced in MOG-abs-positive patients [72.56 (22.71)] compared to MOG-abs-negative MS [80.81 (13.55), p = 0.0128], HCs [103.54 (8.529), p = 0.0014] and NMOSD [88.32 (18.43), p = 0.0353]. Non ON eyes from MOG-abs-positive subjects showed significant subclinical atrophy of temporal pRNFL quadrants. Microcystic macular edema (MME) was observed only in eyes of MOG-abs-positive (24%) and AQP4-abs-positive NMOSD (5.6%), but not in MOG-abs-negative MS or HC ( p < 0.01). MOG-abs may serve as potential marker of retinal degeneration. Specifically, MOG-abs-related OCT features predominate in temporal pRNFL quadrants (resembling the MS retinal pattern), might be more severe than AQP4-abs-positive NMOSD, indicate subclinical pathology, and may be associated with MME.